Direct isolation of genes encoded within a homogeneously staining region by chromosome microdissection. - Su, Y A (1994)
Identification of genes involved in recurring chromosome rearrangements has provided significant insight into the molecular basis of malignancy. We describe here a strategy combining chromosome microdissection and hybrid selection for the direct isolation of chromosome region-specific genes. We modeled this strategy by using sequences recovered from the microdissection of a homogeneously staining region to allow isolation of genes that were overexpressed and present at high copy number within the homogeneously staining region, including the direct isolation of two genes encoded within a 12q homogeneously staining region found in the osteosarcoma cell line OsA-CL. Although first applied to amplified genes, this strategy should be applicable to the isolation of cDNAs from any chromosomal region.